NEO-SALAFISME DI INDONESIA - Eliza Eliza (Universitas Islam Negeri Imam Bonjol Padang, 2015)
The emergence of the reform movement in Indonesia can not be separated from the process of natural change his mind about Islam , since the opening lines of communication with the countries of the Middle East as a center for the development of Islam . The ideas of renewal of the Middle East is , in its development , also rolled to Indonesia — which is often regarded as Islam